Effect of autogenous tooth bone graft with membrane on Class II furcation defects in dogs: A histologic and histomorphometric study - Yang, Keon-Il; Cho, Ah-Young; Yang, Jin-Young; Shin, Hong-In; Lee, Won-Pyo; Kim, Byung-Ock; Yu, Sang-Joun (Oral Biology Research, 2018)
The study evaluated the efficacy of combining autogenous tooth bone grafts with membranes in surgically created class II furcation defects. Thirty teeth of 10 dogs were assessed. Furcation defects (5 × 4 × 3 mm3) were created in the lower third and fourth premolars. Defects in the control, experimental-1, and experimental-2 groups were treated with non-resorbable membranes only, autogenous tooth bone grafts with non-resorbable membranes, and autogenous tooth bone grafts with resorbable membranes, respectively. Healing patterns were observed 4 to 8 weeks after treatment. Mesio-distal sections were obtained and stained with hematoxylin and eosin, and histological and histomorphometrical analyses were performed. Four weeks after treatment, connective tissue and autogenous tooth bone graft materials with newly formed bone were observed. Partial recovery of periodontal ligament-like tissue and formation of cementum-like tissue at root surfaces also occurred. Eight weeks after treatment, mature bone tissue formation was noted. In addition, regular thickness of cementum-like tissue at root surfaces, and improved periodontal ligament-like tissue were observed. Areas of newly formed tissue were 92.2% ± 13.0%, 97.4% ± 4.4%, and 98.1% ± 2.8% at 4 weeks after treatment, and 96.7% ± 3.7%, 96.8% ± 5.7%, and 99.6% ± 0.8% by 8 weeks post-treatment, in the control, experimental-1, and experimental-2 groups, respectively. Regeneration of defective tissues occurred in the experimental group compared with the control group, but not significantly. This study showed that combining autogenous tooth bone grafts with membranes in class II furcation defects improves healing efficiency. KCI Citation Count: 0